Classroom discourse analysis in didactical design of linear equations in one variable: The development of students' critical thinking skills - Tina Yunarti; Jihan Tama Farasiska; Niki Pujarwati; Santy Setiawati (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2025)
This study aims to analyze classroom discourse within the didactical design of linear equations in one variable, focusing on the development of students’ critical thinking skills. The research employed a qualitative approach with an evaluative design. The main participants consisted of one mathematics teacher and 12 seventh-grade students (class VII-1) from a public junior high school in Bandar Lampung during the first semester of the 2024/2025 academic year. The students were grouped according to their mathematical abilities into high, medium, low, and mixed categories. Based on secondary data, the majority of the class consisted of students with low academic ability. Data were collected through observation, interviews, and documentation, while validity was ensured using triangulation techniques. Data analysis was conducted in three stages: data condensation, data display, and conclusion drawing and verification. The findings indicate that (1) the most dominant form of classroom discourse produced by students was questions and answers, highlighting the importance of designing learning activities that facilitate complex questioning and answering to support the development of students’ critical thinking skills; (2) the most frequently observed indicator of critical thinking in classroom discourse was evaluation; and (3) students with medium-level mathematical ability were the most dominant in generating classroom discourse, which was influenced by factors of comfort.